P Pola Makan, Aktivitas Fisik dan Obesitas pada Pekerja Urban di Indonesia: Dietary Patterns, Physical Activity, and Obesity among Indonesian Urban Workers - Rosmiati, Risti; Haryana, Nila Reswari; Firmansyah, Hardi; Purba, Rasita (Amerta Nutrition, 2023)
Background: The increasing prevalence of obesity has become a significant public health concern in Indonesia, particularly among urban workers who often lead sedentary lifestyles and adopt unfavorable dietary patterns. Objectives: To analyze the correlation between dietary patterns, physical activity levels, and obesity among urban workers in Indonesia. Methods: Major dietary patterns were derived using principal component analysis from a 17-item food frequency completed by urban workers in the fifth wave of Indonesia Family Life Survey (IFLS). Self-reported physical activity is assessed by the International Physical Activity Questionnaire (IPAQ). Height and weight were measured to determine nutritional status based on Body Mass Index (BMI), which is then categorized into obese and non-obese urban workers. The association between dietary patterns, physical activity levels, and obesity was analyzed using logistic regression. Results: A total of 10,381 urban workers participated in the study. Four major dietary patterns were identified: a Western dietary pattern characterized by a high intake of fast food, meat, sugary snacks, dairy, and soft drinks; a prudent dietary characterized by fruit and vegetables; a modern dietary pattern characterized by instant noodles, fried snacks, and eggs consumption; and a traditional Indonesian pattern characterized by rice, vegetables, sambal (chili sauce), and fish consumption. Participants adhering to the Western dietary pattern had higher odds of obesity. In contrast, those adhering to the prudent dietary pattern and active physical activity showed lower odds of obesity. Conclusions: Western dietary patterns are associated with an increased risk of obesity, while prudent dietary patterns and active physical activity are inversely associated with obesity in Indonesian urban workers.